3D-printed redox-active polymer electrode with high-mass loading for ultra-low temperature proton pseudocapacitor - Miaoran Zhang; Tengyu Yao; Tiezhu Xu; Xinji Zhou; Duo Chen; Laifa Shen (Advanced Powder Materials)
The stable operation of supercapacitors at extremely low temperatures is crucial for applications in harsh environments. Unfortunately, conventional inorganic electrodes suffer from sluggish diffusion kinetics and poor cycling stability for proton pseudocapacitors. Here, a redox-active polymer poly (1,5-diaminonaphthalene) is developed and synthesized as an ultrafast, high-mass loading, and durable pseudocapacitive anode. The charge storage of poly (1,5-diaminonaphthalene) depends on the reversible coordination reaction of the C=N group with H+, which enables fast kinetics associated with surface-controlled reactions. The 3D-printed organic electrode delivers a remarkable areal capacitance (8.43 ​F ​cm−2 at 30.78 ​mg ​cm−2) and thickness-independent rate performance. Furthermore, the 3D-printed proton pseudocapacitor exhibits great low-temperature tolerance and delivers a high energy density of 0.44 ​mWh cm−2 ​at −60 ​°C, as well as operates well even at −80 ​°C. This work signifies that combining organic material design with 3D hierarchical network electrode construction can provide a promising solution for low-temperature-resistant supercapacitors.